2018
DOI: 10.1111/pre.12344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrients on the growth of a new alpine strain of Haematococcus (Chlorophyceae) from New Zealand

Abstract: SUMMARY The microalga Haematococcus lacustris is a source of astaxanthin used widely in aquaculture, pharmaceutical, and cosmetic industries. A new strain of Haematococcus (LCR‐26C‐1f) isolated from the New Zealand alpine zone was evaluated in this study. The influence of vitamins, micronutrients, various carbon and nitrogen sources were investigated to maximize biomass production in batch cultures using shake flasks. Supplementation of vitamins consisting of thiamine, biotin, and cyanocobalamin improved the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…Parallel experimental studies showed that the addition of a vitamin mix promoted cell growth in our strain (Mazumdar et al. ,b). However, the presence of B 1 (thiamine HCl), B 12 (cyanocobalamin), and B 7 (biotin) in MLA medium would increase large scale cultivation costs.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Parallel experimental studies showed that the addition of a vitamin mix promoted cell growth in our strain (Mazumdar et al. ,b). However, the presence of B 1 (thiamine HCl), B 12 (cyanocobalamin), and B 7 (biotin) in MLA medium would increase large scale cultivation costs.…”
Section: Resultssupporting
confidence: 62%
“…Haematococcus alpinus (strain LCR‐CC‐261f) used in this study is a new species (Mazumdar et al. ,b) and these results constitute the first set of data to compare it with other strains of Haematococcus available in literature.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Microalgae growing under heterotrophic cultivation depend upon metabolism of organic compounds available that will provide carbon source and energy [42] and have a much smaller surface to volume ratio requirement than autotrophic cultivations [43] due to their ability to grow under dark conditions [42].…”
Section: Cultivation Modesmentioning
confidence: 99%